Molecular Mechanisms of Epileptic Encephalopathy Caused by KCNMA1 Loss-of-Function Mutations - Yao, Yu; Qu, Dongxiao; Jing, Xiaoping; Jia, Yuxiang; Zhong, Qi; Zhuo, Limin; Chen, Xingxing; Li, Guoyi; Tang, Lele; Zhu, Yudan; Zhang, Xuemei; Ji, Yonghua; et al. (Frontiers in Pharmacology, 2022)
KCNMA1 encodes the α-subunit of high-conductance calcium- and voltage-dependent (BK) potassium channel. With the development of generation gene sequencing technology, many KCNMA1 mutants have been identified and are more closely related to generalized epilepsy and paroxysmal dyskinesia. Here, we performed a genetic screen of 26 patients with febrile seizures and identified a novel mutation of KCNMA1 (E155Q). Electrophysiological characterization of different KCNMA1 mutants in HEK 293T cells, the previously-reported R458T and E884K variants (not yet determined), as well as the newly-found E155Q variant, revealed that the current density amplitude of all the above variants was significantly smaller than that of the wild-type (WT) channel. All the above variants caused a positive shift of the G-V curve and played a role through the loss-of-function (LOF) mechanism. Then, we used KCNMA1 knockout (BK KO) mice as the overall animal model of LOF mutants. It was found that BK KO mice had spontaneous epilepsy, anxiety, motor impairment, autophagic dysfunction, abnormal electroencephalogram (EEG) signals, and decreased learning memory. In addition, we performed transcriptomic analysis on the hippocampus and cortex of BK KO and WT mice. We identified many differentially expressed genes (DEGs). Six dysregulated genes [i.e., (Gfap and Grm3 associated with astrocyte activation), (Alpl and Nlrp10 associated with neuroinflammation), (Efna5 and Reln associated with epilepsy)] were validated by RT-PCR, which showed a high concordance with transcriptomic analysis. Gene Ontology (GO) analysis showed that DEGs were related to protein labeling, protein binding transcription factor activity, development process and biological adhesion. The kyoto encyclopedia of genes and genomes (KEGG) showed these DEGs were mainly enriched in insulin secretion, axon guidance, p53 signaling pathway, HIF-1 signaling pathway, calcium signaling pathway, cell adhesion molecules (CAMs), ECM-receptor interaction, and phagosome. In conclusion, our study indicated that newly-found point E155Q resulted in a novel loss-of-function variant and the dysregulation of gene expression, especially astrocyte activation, neuroinflammation and autophagy, might be one of the major mechanisms induced-epilepsy.